Monetary policy in a bipolar international monetary system - Sinimaaria Ranki (Bank of Finland, 1998)
The study deals with the international transmission of economic shocks, their consequences for exchange rates and the reconciliation of exchange rate management with monetary policy. The theoretical part of the study consists of a mainstream model of two large, interdependent economies with special emphasis on the effects of various shocks on the inflation rate and exchange rate. The empirical application uses US and German data to shed light on the exchange rate implications of the choices faced by European and US monetary policymakers.The results suggest that the inflation rate is dominated by domestic supply shocks in both economies studied.When such shocks raise the domestic price level, the currency also depreciates.This aspect of the results means that, from a single-country perspective, monetary policy measures aimed at stabilizing the price level can be compatible with stabilization of the exchange rate as well.However, from the viewpoint of the other country, a conflict emerges between exchange rate and price stability.This difference causes a dilemma in international monetary coordination.Allowing that exchange rate considerations affect monetary policy, the situation is further complicated by the fact that exhange rate volatility seems to be for the most part independent of the economic fundamentals included in the study.
URN:NBN:fi:bof-20140807471
Keywords: 330; euro; monetary policy; exchange rate; shock transmission